2009
DOI: 10.1021/jo9008172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies and Improvement of Coinage Metal-Catalyzed Transformation of Alkynyloxiranes to Furans: An Alcohol Addition−Cyclization−Elimination Cascade

Abstract: In the presence of alcohol Ag or Au salts or complexes catalyze the conversion of alkynyloxiranes to substituted furans. Both catalysts are effective, and a large furan diversity can be obtained in high yield with one or the other catalyst. Mechanistic studies revealed that a cascade pathway and not the sometimes reported direct intramolecular nucleophilic addition of oxirane oxygen atom to intermediate acetylene-metal pi-complex occurs. Under the defined conditions, the intermediate formation of epoxide openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 63 publications
0
41
0
1
Order By: Relevance
“…[13] Following this simple sequence,( AE)-pallescensin A( 16)w as synthesized in just 3s teps from triflate 10 a (4 steps from dienyne derivative 9a)i n4 0% global yield. Again, the entire sequence could be performed on ag ram-scale (1.1 go fp allescensin Ai no ne batch) and without any purification of the intermediates (just af inal column chromatography).…”
Section: Methodsmentioning
confidence: 99%
“…[13] Following this simple sequence,( AE)-pallescensin A( 16)w as synthesized in just 3s teps from triflate 10 a (4 steps from dienyne derivative 9a)i n4 0% global yield. Again, the entire sequence could be performed on ag ram-scale (1.1 go fp allescensin Ai no ne batch) and without any purification of the intermediates (just af inal column chromatography).…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the reaction proceeds via a ring opening to form products 2-399a and 2-399b , both of which cyclize under the reaction conditions in the presence of the Au(I)-catalyst to provide furans 2-398 (Scheme 110). 202 …”
Section: Synthesis Of Furansmentioning
confidence: 99%
“…A single example of this reaction catalyzed by the AgOTf/TsOH system was later reported by the same group. 202 …”
Section: Synthesis Of Furansmentioning
confidence: 99%
“…The generally accepted mechanism involves the activation of the alkyne group by coordination to the metal followed by attack of the epoxide at the distal Csp center, forming a Csp 2 -gold σ-bond. After the loss of a proton the furan product would be generated as shown in Scheme 82 151 However, mechanistic studies later on showed that the reaction might proceed through a cascade process involving epoxide opening either by adventitious water or alcohol used in the reaction, followed by cyclization and elimination of alcohol as depicted in Scheme 83 152 .…”
Section: Epoxidesmentioning
confidence: 99%